2013
DOI: 10.5897/ajpp2013.3471
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic effects of Moringa oleifera methanolic leaf extract in chickens infected with Newcastle disease virus (kudu 113) strain

Abstract: This study was aimed at evaluating the immune boosting potential of crude methanolic extract of Moringa oleifera in chickens experimentally challenged with Newcatle disease (ND) virus. One hundred and twenty forty two (42) day old chicks were randomly divided into four equal groups. Groups I and II were given daily oral treatment of methanolic extract of M. oleifera at 200 mg/kg body weight until day 56 of age. Groups II and III were vaccinated with the La Sota strain of ND vaccine. Group I was not vaccinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The study of Yang et al (2006) showed that dietary dehydrated leaves of Moringa induce a significant increase in the concentrations of total globulin, γ-globulin and lymphocyte ratio, antibody titer levels with comparison to the standard (sheep erythrocytes), and delayed-type hypersensitivity of broiler chickens. Comparable results also were obtained by Chollom et al (2012), Eze et al (2013), Hossam et al (2016) and Younis and Elbestawy (2017) who demonstrated that M. oleifera extracts have nutritional value as well as strong antiviral activity against ND virus. Means with different superscripts, within age, are significantly different (P < 0.05)…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The study of Yang et al (2006) showed that dietary dehydrated leaves of Moringa induce a significant increase in the concentrations of total globulin, γ-globulin and lymphocyte ratio, antibody titer levels with comparison to the standard (sheep erythrocytes), and delayed-type hypersensitivity of broiler chickens. Comparable results also were obtained by Chollom et al (2012), Eze et al (2013), Hossam et al (2016) and Younis and Elbestawy (2017) who demonstrated that M. oleifera extracts have nutritional value as well as strong antiviral activity against ND virus. Means with different superscripts, within age, are significantly different (P < 0.05)…”
Section: Resultssupporting
confidence: 55%
“…Leaf powder of M. oleifera is considered as chep source of poultry ration protein (Tesfaye et al, 2013), in addition to vitamins, acids, minerals, and various phenolics compounds (Moyo et al, 2012). Dietary supplementation of poultry with M. oleifera leaf powder (MOLP) improved the body performance traits (Okafor et al, 2014;Mousa et al, 2017), as well as enhanced both the intestinal health (Gomashe et al, 2014) and the humoral immune response (Eze et al, 2013 and.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was in close agreement with Younis et al (2016) who indicated that Ross 308 breed fed 2% and 3% MOLM showed an increased immunity against ND than Cobb 500 breed and control birds. Also, Eze et al (2013) indicated that methanolic extract of M. oleifera at 200 mg/kg body weight increased ND HI titer in the vaccinated and un-vaccinated chicken groups and it could be recommended as an immune-booster treatment against ND in non-vaccinated birds. In the same trend, Chollom et al (2012) revealed that M. oleifera seed extract had a strong antiviral activity against ND in ovo.…”
Section: Immune Responsementioning
confidence: 99%
“…al., 2014) and immune responses (Du et al, 2007;Yang et al, 2007;Eze et al, 2013;Younis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Methanol extracts of fruits of Solanum xanthocarpum showed pronounced immunoprotective activity by increasing the depleted levels of total WBC count and RBC, percentage Hb, and percentage neutrophils adhesion in mice treated with cyclophosphamide at a dose of 30 mg/kg body weight (Rokeya et al, 2011;Gupta et al, 2010), in their study, demonstrated the immunomodulatory property of ethanolic (50%) extract of Moringa oleifera leaves on immune-supressed rats. Eze et al (2013), while studying the immunologic effects of M. oleifera methanolic leaf extract in chickens infected with Newcastle disease virus discovered that the extract stimulated the production of white blood cells. The result showed a dose dependent increase in total WBC and percentage neutrophil counts by an action on both the cellular and humoral immunity when the result is compared to the control group, Hence, the test herbal products are said to be immunostimulatory in action.…”
Section: Treatmentmentioning
confidence: 99%